Kinerja Sumber Daya Manusia di Rumah Potong Hewan (Studi Kasus RPH Kategori I dan Kategori II) - N. A. D. Tiya; H. Nuraini; L. Cyrilla E. N. S. D (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2021)
This study aims to identify the characteristics of human resources in slaughterhouses category I andcategory II, as well as to analyze the performance and efficiency of human resources in slaughterhousescategory I and category II. Location samples and respondents were determined purposively. Thevariables observed were the characteristics of my human source, my human source performance, andthe efficiency of my human source performance in category I and category II slaughterhouses. Theresults showed that the characteristics of category I and category II employees had an average highschool education, 30-40 years of age and 10-20 years of work. The performance of my human resources(work results, skills, discipline and responsibility) of each slaughterhouse has a fairly good percentage,slaughterhouse for category I (77.66-80.95%) and slaughterhouse for category II (81.68-83.59%) . Theperformance efficiency figures for the employees of the slaughterhouse category I and category II aresimilarly close to number 1 indicating that the employees’ working time is used efficiently.